Extrapulmonary Clinical Manifestations in COVID-19 Patients - Sarkesh, Aila (Am J Trop Med Hyg, 2020)
COVID-19 manifestations in symptomatic patients can be in the form of pneumonia, acute respiratory syndrome, and multiple organ dysfunction as well. Renal complications, gastrointestinal dysfunctions, endocrine system disorders, myocardial dysfunction and arrhythmia, neurological dysfunctions, dermatological symptoms, hematological manifestations, and thromboinflammation are among the reported extrapulmonary complications. Moreover, the presence of coagulopathy, excessive and dysregulated immune responses, and autoimmunity by COVID-19 patients is considerable. The pathogenesis of infection entails the entry of the virus via receptors on cells, principally angiotensin-converting enzyme 2 receptors. Direct virus damage coupled with indirect effects of viral infection including thromboinflammation, dysfunction of the immune system, and dysregulation of the renin–angiotensin system leads to multiple organ failure. This review outlines the extrapulmonary organ–specific complications and their pathophysiology and epidemiology.